"Know What to Answer the Epicurean": A Diachronic Study of the ʾApiqoros in Rabbinic Literature - Labendz, Jenny R. (Hebrew Union College annual, 2003)
This essay traces rabbinic usage and understanding of the term ʾapiqoros from tannaitic literature through the redactional layer of the Babylonian Talmud, showing that sources identified as tannaitic, amoraic, and editorial reflect a sequential, conceptual development in the term's usage. While the word ʾapiqoros is used colloquially today to refer to a Jewish heretic or dissenter, it meant something much more specific in tannaitic literature, and its meaning evolved and changed considerably after that period. While tannaim associated the ʾapiqoros with Greek philosophy, amoraim placed the term in the context of disrespect for Torah, and, still later, the editor of the Bavli conflated it with a phonetically similar Aramaic word for irreverence. The essay thus serves as a useful demonstration of how intellectual history can be traced using rabbinic sources.